Digital identities creating and communicating the online self - Cover, Rob (Amsterdam ; Boston Academic Press/Elsevier, 2016)
Online Identities: Creating and Communicating the Online Self presents a critical investigation of the ways in which representations of identities have shifted since the advent of digital communications technologies. Critical studies over the past century have pointed to the multifaceted nature of identity, with a number of different theories and approaches used to explain how everyday people have a sense of themselves, their behaviors, desires, and representations. In the era of interactive, digital, and networked media and communication, identity can be understood as even more complex, with digital users arguably playing a more extensive role in fashioning their own self-representations online, as well as making use of the capacity to co-create common and group narratives of identity through interactivity and the proliferation of audio-visual user-generated content online.
Understanding identity online : social networking -- Performativity, communication, and selfhood -- Interactivity, digital media, and the text -- Bodies, identity, and digital corporeality -- Identity, Internet, and globalization -- Mobile telephony, mobility, and networked subjectivity -- Online selves : digital addiction -- Digital surveillance, archives, and Google Earth : identities in/of the digital world.
Ma. Theresa Q. Tabada (Recommending faculty) - Bookfair2017
Includes bibliographical references (pages 267-282) and index.
Keywords: Internet -- Social aspects; Online identities